2022
DOI: 10.1186/s12866-022-02681-0
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal microbiota in women with spontaneous preterm labor versus those with term labor in Kenya: a case control study

Abstract: Background Preterm birth is a global problem with about 12% of births in sub-Saharan Africa occurring before 37 weeks of gestation. Several studies have explored a potential association between vaginal microbiota and preterm birth, and some have found an association while others have not. We performed a study designed to determine whether there is an association with vaginal microbiota and/or placental microbiota and preterm birth in an African setting. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The cervicovaginal environment of approximately 16% of pregnant women in Pemba Island, Tanzania, are colonized by at least three of four STI (sexually transmitted infection) infectious agents (i.e., Chlamydia trachomatis , Trichomonas vaginalis , Neisseria gonorrhoeae , and Mycoplasma genitalium ); therefore, adverse pregnancy outcomes may not necessarily be instigated by a single infectious agent ( 79 ). In Kenya, more than fifty percent of the vaginal microbiota consisted of Gardnerella and/or Prevotella , with lactobacilli ranging from 1% – 99%, but without a clear link between variation in composition and term or sPTB ( 94 ). In a longitudinal study involving pregnant Nigerian women (n=38), the prevalent cervicovaginal bacterium was L. iners ( 40 ).…”
Section: Introductionmentioning
confidence: 99%
“…The cervicovaginal environment of approximately 16% of pregnant women in Pemba Island, Tanzania, are colonized by at least three of four STI (sexually transmitted infection) infectious agents (i.e., Chlamydia trachomatis , Trichomonas vaginalis , Neisseria gonorrhoeae , and Mycoplasma genitalium ); therefore, adverse pregnancy outcomes may not necessarily be instigated by a single infectious agent ( 79 ). In Kenya, more than fifty percent of the vaginal microbiota consisted of Gardnerella and/or Prevotella , with lactobacilli ranging from 1% – 99%, but without a clear link between variation in composition and term or sPTB ( 94 ). In a longitudinal study involving pregnant Nigerian women (n=38), the prevalent cervicovaginal bacterium was L. iners ( 40 ).…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that the diversity of the vaginal microbiome may play a role in the risk of preterm birth, were women with decreased levels of protective bacterial species and increased levels of harmful bacteria may be at greater risk. In contrast to these findings, a study conducted in an African population showed no association between preterm birth and the composition of the vaginal community [ 93 ]. Differences observed between these studies may be due to sample size and ethnicity.…”
Section: The Microbiome In Pregnancy Complicationsmentioning
confidence: 87%
“…These findings emphasize the need for dental hygiene as an integral component of prenatal care. Recently, the placental microbiome has been associated with preterm birth [ 95 , 96 ], although conflicting findings exist [ 93 , 97 ]. Discrepancies observed between studies may be due to difficulty in recovering viable DNA samples from the placenta or the detection of low bacterial loads that are indistinguishable from negative controls or potential sources of contaminants.…”
Section: The Microbiome In Pregnancy Complicationsmentioning
confidence: 99%
“…VD is a severe challenge worldwide in women’s health leading to infertility, pregnancy loss and major obstetrical complications such as PPROM and preterm labor. 7 , 8 , 24 Moreover, due to high recurrence rates and increasing resistance to antibiotics, there is a need to develop alternative and durable treatments for this condition. 1 , 12 , 13 Ideally, a therapy without the use of antibiotics could prove to be a better and potentially more sustainable solution.…”
Section: Discussionmentioning
confidence: 99%